Mejoramiento del cuidado de los bosques aledaños del centro poblado de Pucallpa, distrito de Indiana, provincia de Maynas - 2021 mediante capacitación ambiental - Ruiz Rodríguez, Jorge Elmer (2022)
This research work was carried out in the town of Pucallpa, district of Indiana, province of Maynas, Loreto region, with the purpose of determining the current situation of the care of the surrounding forests of the town center of Pucallpa of the district of Indiana, province of Maynas, through environmental training. According to the results, the total number of people surveyed is 52 (100%), 36 (69%) are male and 16 (31%) are female, most of whom are among 18 and 40 years old. The level of education is 13% of illiterate men and 2% of women, 33% of men and 17% of women have primary education, 19% of men and 12% of women have secondary education, and only 4% have higher education in values and there are no women with superior instruction. Seven (7) out of 10 people know the importance of the forest and only 3 out of 10 people do not know about it. The environmental values in the population are poor, only 23% of the population has environmental values and 67% do not have them. The authorities and residents have little interest in training residents on environmental issues, only 22% show concern on the subject. The population does not have infrastructure, tools and equipment to develop silvicultural tasks.